HEALTH DAMAGE TO CIVIL CONSTRUCTION WORKERS DUE TO USE AND EXPOSURE TO CEMENT - Robert Audrik Almeida Nunes; David Barbosa De Alencar; Camily Murrieta Vasconcelos Oliveira Bezerra; Igor Felipe Oliveira Bezerra (ITEGAM-JETIA, 2019)
Civil construction has great representation for the socioeconomic development of our country. However, it is an activity that, if not carried out within the safety standards required by our labor legislation, provides great trends for labor incidents. The present work aims to address the risks inherent to the misuse of cement in the construction industry for the health of workers, having seen, because cement is a chemical agent that can be inhaled through the respiratory tract or, due to direct contact. with the skin and mucous membranes, and also, by oral intake, provides the severe emergence of pathologies in the health of workers submitted to continuous contact with it. Initially, it will be presented characteristics of this material, as well as some examples of pathologies associated with the use of the product and, finally, emphasize the importance of the use of safety and prevention measures capable of avoiding the referred damages to the workers health. For this, we used the methodology of bibliographic research in scientific sources already consecrated referring to the theme dissertated here that allow to prove the theme treated here. Thus, with the conclusion of the subject, it is concluded that it is necessary to use all necessary safety measures to ensure the development of the activity, but especially to ensure the integrity and health of workers who are in continuous contact with the cement.